Increased serum levels of B cell activating factor (BAFF) in subsets of patients with idiopathic inflammatory myopathies. Issue 6 (15th July 2008) - Kryštůfková, O; Vallerskog, T; Helmers, S Barbasso; Mann, H; Půtová, I; Běláček, J; Malmström, V; Trollmo, C; Vencovský, J; Lundberg, I E
Abstract : Objective: To investigate serum levels of B cell activating factor (BAFF) in patients with myositis and correlate these to autoantibody profile, clinical phenotype and treatment. Methods: BAFF levels in sera from 49 patients with dermatomyositis, 44 with polymyositis, 6 with inclusion body myositis and 30 matched controls were measured by ELISA. Specific autoantibodies were detected by line blot and western blot assays. Results: Serum levels of BAFF were significantly higher in patients compared to healthy controls (p = 0.003). Patients with anti-Jo-1 autoantibodies had higher BAFF levels than control individuals (p<0.003) or patients without any specific autoantibodies (p<0.05). Patients with dermatomyositis had higher BAFF levels compared to polymyositis (p<0.05). Patients with interstitial lung disease (ILD) had higher BAFF levels than patients without ILD (p<0.05) or controls (p<0.01) but this could be explained by presence of anti-Jo-1 autoantibodies. BAFF levels correlated with serum creatine kinase (CK) (rs = 0.365, p = 0.0005) but not with C-reactive protein (CRP) levels. A negative correlation of BAFF levels with glucocorticoid daily dose for all patients (rs = −0.292, p = 0.003) and with cumulative glucocorticoid doses in early myositis cases (rs = −0.659, p<0.001) was recorded. Conclusion: Our finding of elevated serum levels of BAFF in patients with myositis with described phenotypes together with the correlations between levels of BAFF and CK and a negative correlation with dose of glucocorticoids, indicate that BAFF could be a potential therapeutic target in such cases.